PERIOPERATIVE INCIDENCE OF IATROGENIC GALLBLADDER PERFORATION DURING LAPAROSCOPIC CHOLECYSTECTOMY IN SULAIMANIYAH TEACHING HOSPITAL - Tofiq, Sarkhel Hama; Shareef, Seerwan Hama (Journal of Sulaimani Medical College, 2022)
Background Iatrogenic perforation of the gallbladder has been reported in 28% of those patients who undergo laparoscopic cholecystectomy. It has been pointed out that gallbladder perforation can result in spillage out gallstones and bile. Objectives To investigate the perioperative incidence of iatrogenic gallbladder perforation during laparoscopic cholecystectomy in Sulaimani Teaching Hospital. Patients and Methods The present investigation was a single-centre, prospective observational study that was carried out in Sulaimani Teaching Hospital in 2018-2019. The study sample included 99 patients who had undergone elective cholecystectomy by multiple surgeons. Required data on the possible risk factors and early outcomes and the patients’ demographics, including age, BMI, and gender, were collected. The collected data were analyzed through the Statistical Package for the Social Sciences (version 22.0). Results The results revealed that 80% of the patients were females. Also, 42.4% had no chronic diseases. At the same time, diabetes mellitus (DM), DM along with hypertension (HT), and HT were the most prevalent chronic diseases among them with 18.2%, 16.2%, and 10.1% of prevalence, respectively. (Multiple attacks of cholestasis). Only 17.2% of the patients had an abdominal operation before, and acute cholestasis and chronic cholestasis were seen respectively in 13% and 17% of them. The most common causes of gallbladder perforation (GP) were found to be electrocautery (16.2%) and grasper (7.1%). 33.3% of the patients were overweight (BMI between 25 and 29.9), 45.5% were obese (BMI between 30 and 34.9), and 20.2% had a BMI of over 35. (Overweight or obese patients have a problematic view in laparoscopy) Most of the patients were aged 30 to 49 (62.6%). A majority of the patients (94.9%) were found to have gallstones. Conclusion Iatrogenic gallbladder perforation is prevalent among patients who undergo laparoscopic cholecystectomy. However, laparoscopic cholecystectomy is still a better choice and is associated with fewer complications than open cholecystectomy. Required measures need to be adopted for patients with perforated gallbladder to minimize spillage and remove as much spilt gallbladder content as possible.
Keywords: Iatrogenic gallbladder perforation; Laparoscopic cholecystectomy; Gallstone; Spillage of bile